Compact intra-cavity pumped low-threshold passively Q-switched Ho:Sc2SiO5 laser by a LD-pumped Tm:YAP laser at room temperature. (24th July 2017) - Yang, Xiao-tao; Xie, Wen-qiang; Liu, Long; Li, Lin-jun
Abstract: A compact intra-cavity pumped low-threshold passively Q-switched (PQS) Ho:Sc2 SiO5 (Ho:SSO) laser is reported for the first time. The Tm:YAlO3 (Tm:YAP) crystal and the Ho:SSO crystal are placed in the same laser cavity. A laser diode with a central wavelength of 793 nm is used to realize the output of the Ho:SSO laser. Both the continuous wave (CW) and PQS operation are investigated. A Cr 2+ :ZnSe is used as the saturable absorber in the PQS Ho:SSO laser. For the CW mode, the laser threshold is only 750 mW, which is 980 mW in the PQS mode. A maximum pulse energy of 699 µ J is primarily obtained, corresponding to the pulse width of 96 ns. The maximum repetition frequency is 1.46 kHz. The maximum pulse peak power can be calculated to be 7.28 kW. The beam quality factor M 2 is calculated to be 1.4 with the maximum output power.